2008
DOI: 10.4319/lo.2008.53.3.1111
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the growth response of Cladophora in a Laurentian Great Lake to the exotic invader Dreissena and to lake warming

Abstract: A Cladophora growth model (CGM) is calibrated and validated here to simulate attached and sloughed Cladophora biomass in daily time-steps in an urbanized location of Lake Ontario, using two years of collected input data and independent measurements of Cladophora biomass. The CGM is used to hindcast Cladophora growth using multiplicative factors of seasonal minimal tissue phosphorus concentrations (Q P ) and seasonal mean nearshore light attenuation (Kd PAR ) of the early 1970s and 1980s relative to modern data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 45 publications
1
91
0
Order By: Relevance
“…Our growth rates measured as change in shell length generally fell within the ranges reported for upstream Lake Erie (MacIsaac 1994;Stoeckmann 2003). As expected, our reported mean near-bottom Chl a concentrations during expt 1, calibrated at Shallow and Middle stations, were somewhat higher on average than extracted Chl a concentrations previously reported from near-surface waters in the same study area during the same season (Malkin et al 2010). No comparable extracted Chl a data from near-bottom water exist from during expt 1.…”
Section: Methodsmentioning
confidence: 34%
See 2 more Smart Citations
“…Our growth rates measured as change in shell length generally fell within the ranges reported for upstream Lake Erie (MacIsaac 1994;Stoeckmann 2003). As expected, our reported mean near-bottom Chl a concentrations during expt 1, calibrated at Shallow and Middle stations, were somewhat higher on average than extracted Chl a concentrations previously reported from near-surface waters in the same study area during the same season (Malkin et al 2010). No comparable extracted Chl a data from near-bottom water exist from during expt 1.…”
Section: Methodsmentioning
confidence: 34%
“…In the littoral zone, dreissenid mussels are a dominant source of soluble reactive phosphorus (Ozersky et al 2010;Turner 2010), and thereby may contribute to a nutrient gradient from depth. Furthermore, mussels have likely increased light penetration in the coastal zone through their persistent filtration (Malkin et al 2008) and/or by reducing the frequency of calcite precipitation (i.e., 'whiting events'; Barbiero et al 2006). Taken together, dreissenid mussels may be promoting development of a deeper DCM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were taken at depths of 0.5, 1.5, 3.0, and 5.0 m at times of peak Cladophora biomass (June-August) along the shores of Oakville, Whitby, Cobourg, Presqu'ile, Point Petre, Bath, and Emeric Point (all on Lake Ontario). Additional Lake Ontario biomass values used in this study were reported by Malkin et al (2008;biomass in 2004 and at Oakville, Ontario), Higgins et al (2008; …”
Section: Beach Closuresmentioning
confidence: 99%
“…C. laetevirens, C. sericea, C. glomerata (7-9 ) (Smith et al, 2005;Malkin et al, 2008;Gubelit and Berezina, 2010;Balkıs et al, 2013).…”
Section: Effects Of Environmental Factors On Zoospore Release and Earlymentioning
confidence: 99%